2019
DOI: 10.1093/neuros/nyz321
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Sarcoma of the Nerve—Clinical and Pathological Features: Case Series and Systematic Review

Abstract: BACKGROUND Synovial sarcoma of the nerve is a rare entity with several cases and case series reported in the literature. Despite an improved understanding of the biology, the clinical course is difficult to predict. OBJECTIVE To compile a series of patients with synovial sarcoma of the peripheral nerve (SSPN) and assess clinical and pathological factors and their contribution to survival and recurrence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
2
0
1
Order By: Relevance
“…Therefore, a high rate of local recurrence and metastasis was observed, while data showed that the survival rate was 20% to 50% in the last 5 years. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a high rate of local recurrence and metastasis was observed, while data showed that the survival rate was 20% to 50% in the last 5 years. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 According to the reported series, the main symptoms are neuropathic and local pain, motor deficit, and palpable mass; in our patient, the insidious symptomatology and history of rheumatic disease delayed the diagnosis. 3 …”
Section: Discussionmentioning
confidence: 99%
“… 1 2 De acordo com a série relatada, os principais sintomas são dor neuropática e local, déficit motor e massa palpável; em nosso paciente, a sintomatologia insidiosa e a história da doença reumática atrasaram o diagnóstico. 3 …”
Section: Discussionunclassified